Tinjauan Yuridis Jual Beli Tanah tanpa melalui Pejabat Pembuat Akta Tanah/PPAT: Studi Kasus Putusan Nomor 101/PDT.G/2020/PN TIM - Anwar Susanto; Zaenal Arifin (Sekolah Tinggi Ilmu Hukum Prof Gayus Lumbuun, 2023)
This research was conducted with the aim of finding out how the validity of the status of buying and selling land which was carried out without a deed by the Land Deed Making Officer (PPAT) and how the settlement can be done by the buyer, so that buying and selling land carried out without a PPAT deed can have definite legal force. By using the normative juridical research method, it can be concluded that in buying and selling land which is carried out without a deed, the official making the land deed is a legal sale and purchase as long as it fulfills Article 1338 and Article 1320 of the Indonesian Civil Code, the problem faced is only a matter of proof in in the trial later, the settlement that can be carried out by the buyer, so that the sale and purchase of land carried out without a PPAT deed can have definite legal force by asking for a District Court Decision which gives legal certainty to the plaintiff as the legal owner of the land and buildings on it. With the decision of the District Court, the PPAT as the original holder of the certificate is required to submit the certificate for the land in question which is still registered in the name of the defendant to the plaintiff and his attorney. Because the defendant's place of residence is no longer known so that he cannot appear before the PPAT, the District Court's decision also gives permission and power of attorney to the plaintiff to act on behalf of the defendant (seller) in carrying out the signing of the deed of sale and purchase of land while simultaneously acting for and on his own behalf. the buyer at the price agreed at the time the sale and purchase of the lawsuit was carried out.